A Descriptive Study of Hepatitis B Surface Antigenemia (HBsAg) among Pregnant Women in Southern Nigeria - Utoo Bernard Terkimbi (Highlights on Medicine and Medical Science Vol. 1, 2021)
Background: Hepatitis B virus (HBV) infection is one of the most common public health issues worldwide. HBV-related chronic liver disease claims the lives of over one million people per year. In endemic areas, maternal to foetal transmission from chronic carriers reaches 90%, accounting for up to 40% of the world’s chronic carriers. Methods: This was a descriptive study which involved Serial recruitment of 836 women attending the antenatal clinic at a health facility in Cross-River State, Nigeria. HBsAg screening was done using an ELISA test. Results: Fifty five (6.6%) of the 836 women screened tested positive for HBsAg. The mean age and parity of sero-positive subjects was 26.9 ±5.0 (range 18-38 years) and 2.2±1.2 (0 to 5) respectively. The prevalence was more in women who were farmers (29.1%) and those with either none or low level of formal education (67.2%). Conclusion: There is a 6.6 percent sero-prevalence rate among pregnant women. It is recommended that women’s education, economic empowerment, and public awareness programmes with an emphasis on changing risky social lifestyles be implemented. Efforts to facilitate regular prenatal screening, immunisation, and child vaccination should be maintained.